2011
DOI: 10.1186/1471-2105-12-66
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of disordered proteins in prokaryotes

Abstract: BackgroundA significant number of proteins have been shown to be intrinsically disordered, meaning that they lack a fixed 3 D structure or contain regions that do not posses a well defined 3 D structure. It has also been proven that a protein's disorder content is related to its function. We have performed an exhaustive analysis and comparison of the disorder content of proteins from prokaryotic organisms (i.e., superkingdoms Archaea and Bacteria) with respect to functional categories they belong to, i.e., Clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 47 publications
5
39
0
Order By: Relevance
“…The fact that no IDRs were found in mitochondrial proteins [67][68][69] supports our hypothesis that certain, crucial TRs were generated before endosymbiosis of Prokaryotes and persisted within the proteins. If initially disordered regions were accumulated in proteins through alternative splicing or exonization, and by duplication established a stable tertiary structure, they might have been missed by the disorder detection methods.…”
Section: Tandem Repeats Originate Through Duplicationsupporting
confidence: 72%
“…The fact that no IDRs were found in mitochondrial proteins [67][68][69] supports our hypothesis that certain, crucial TRs were generated before endosymbiosis of Prokaryotes and persisted within the proteins. If initially disordered regions were accumulated in proteins through alternative splicing or exonization, and by duplication established a stable tertiary structure, they might have been missed by the disorder detection methods.…”
Section: Tandem Repeats Originate Through Duplicationsupporting
confidence: 72%
“…161 A computational analysis of disorder in prokaryotes has corroborated the higher abundance of disorder in Bacteria as compared to Archaea. 274 Moreover, in agreement with the low abundance of disorder in prokaryotes, none of the 13 mitochondrial-encoded proteins are disordered. 161 Systematic analysis of IDP occurrence in 53 archaeal species showed that disorder content is highly species-dependent.…”
Section: Evolutionmentioning
confidence: 81%
“…2,3 Lacking of a well-defined three-dimensional structure, IDPs have posed a serious challenge for structural biologists as their function is directly related to their conformational dynamics in solution.…”
Section: Introductionmentioning
confidence: 99%